2002
DOI: 10.1021/jf0116496
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Iron Bioavailability from 15 Rice Genotypes:  Studies Using an in Vitro Digestion/Caco-2 Cell Culture Model

Abstract: An in vitro digestion/Caco-2 model was used to compare iron bioavailability from 15 selected Fe-dense and normal genotypes of unpolished rice from the International Rice Research Institute. Iron uptake was determined using Caco-2 cell ferritin formation in response to exposure to a digest of the cooked rice. Iron bioavailabilities from all rice genotypes were ranked as a percent relative to a control variety (Nishiki). Iron concentration in the rice samples ranged from 14 to 39 microg/g. No correlation was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 21 publications
10
108
0
2
Order By: Relevance
“…Limited studies on seed-Fe and -Zn concentration and bioavailability in maize, rice, and wheat revealed no such associations (Glahn et al 2002;Oikeh et al 2003aOikeh et al ,b,2004a, indicating that it is possible to significantly increase both concentration and bioavailability of either Fe or Zn in the seed by breeding and selection.…”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 99%
“…Limited studies on seed-Fe and -Zn concentration and bioavailability in maize, rice, and wheat revealed no such associations (Glahn et al 2002;Oikeh et al 2003aOikeh et al ,b,2004a, indicating that it is possible to significantly increase both concentration and bioavailability of either Fe or Zn in the seed by breeding and selection.…”
Section: B Genotype â Environment Interaction and Relationships Betwmentioning
confidence: 99%
“…The protocol was developed by modifying the method of Glahn et al and Laurent et al [19][20][21][22]. Fresh (4 g) or freeze-dried (1 g) banana and sweet potato were ground with a food chopper from Zyliss Ò (Oxenford, Australia), applying ten pressures for all samples to simulate mastication.…”
Section: In Vitro Model For Human Digestionmentioning
confidence: 99%
“…To assess potential bioavailability, in vitro digestion/Caco-2 cell culture models have been developed in recent years. The model modified from Glahn et al and from Laurent et al has been used in the current study [19][20][21][22]. In vitro digestion simulates the physiochemical and biochemical conditions encountered in the gastrointestinal tract and is used to estimate the rate and extent of release of bioactive compounds from the food matrix into the intestinal lumen (bioaccessibility) and therefore potentially available for uptake.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as a powerful antioxidant that has been demonstrated to reduce atherosclerotic plaque formation, a risk factor associated with cardiovascular disease (Ling et al, 2001). On the negative side, proanthocyanidin pigments reduce the bioavailability of iron, protein, and carbohydrates (Eggum et al, 1981;Carmona et al, 1996;Glahn et al, 2002), which has important implications for people with low nutritional status. A better understanding of the genetics and molecular biology of red pericarp and the association of this characteristic with other wild/weedy traits will provide important information for the better management of both the negative and positive features associated with red rice.…”
Section: Introductionmentioning
confidence: 99%